PENGARUH LAMA PERENDAMAN DAGING SAPI DALAM BLEND JAHE (Zingiber officinalle Roscoe) TERHADAP pH dan KEEMPUKAN - Suratno Suratno; Ali Husni; Rr Riyanti; Dian Septinova (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This study aimed to determine the effect of soaking time for beef meat in ginger blend (Zingiber officinale Roscoe) on pH and tenderness. This research was conducted at the Animal Production and Reproduction Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. Meat samples were obtained from Z-Beef slaugher house at Bandarlampung. The study used an experimental method in a completely randomized design with four treatments and five replications using a 15% ginger blend solution. The treatments were beef meat without soaking, soaking for 10 minutes, 20 minutes and 30 minutes with ginger blend. The results obtained were analyzed with Analysis of Variance (ANOVA) at 5% significance level and continued with the Least Significant Difference test (LSD test). The results showed that the soaking time with ginger blend had no significant effect (P>0.005) on the pH value, but it had a significant effect (P<0.005) on the tenderness of beef meat with soaking time was up to 30 minutes. Key words: Beef, Ginger, Soaking time, pH, and tenderness